Co‐Designing Aphasia Services: Evaluation of Involvement and Processes to Support Inclusion of People With Post Stroke Aphasia. - Anemaat, Lisa; Copland, David A.; Palmer, Victoria J.; Wallace, Sarah J. (Health Expectations, 2025)
Background: People with aphasia (PWA, impaired language/communication) are often excluded from research that concerns them due to a lack of methodological adaptations to support communication. This paper describes adaptations to support their involvement in experience‐based codesign (EBCD). Aims: To describe the involvement of PWA in EBCD and critically evaluate adaptations required to support involvement. Methods: Mixed methods process evaluation and reflexive critical appraisal with PWA, significant others (SO), and speech pathologists (SP). Using surveys, stakeholders (n = 127) and a consumer advisory group (CAG; n = 6) provided feedback on involvement in five stages of the research: (1) online interviews and focus groups; (2) online surveys; (3) consensus meetings; (4) codesign workshops; and (5) the CAG. Critical reflections (lead researcher) informed the analysis. Descriptive statistics and inductive content analysis were used. Results: Most PWA (79%) liked sharing their experiences online, and contributed as much as desired in group meetings (64%). A modified touchpoint film approach (use of voice actors, still images, and subtitles) supported reflexive discussions and collaborative understanding. All PWA and SO, and most SPs (78%) thought the touchpoint film helped them to understand experiences of care and areas for change. Long‐term engagement in the project was perceived to help build relationships, reduce hierarchical power differentials and support equal sharing of ideas. Conclusions: Meaningful involvement of PWA was supported through long‐term engagement, a modified touchpoint film approach, and hybrid methods of data collection. EBCD is a suitable approach for exploring experiences of care, identifying leading priorities, and co‐designing areas for change with PWA. Patient or Public Contribution: This evaluation is informed by the reflections of the research team. This team included the consumer advisory group (public involvement team members) comprising PWA (n = 3), SOs (n = 2) and a Cultural Capability Officer. Research team members (LNA, DAC, VJP, and SJW) designed the study (including research questions, data analysis processes and assessment measures). Public involvement guided study procedures and recruitment (e.g., methods for engaging with people with lived experience of aphasia), and the interpretation and dissemination of results (e.g., co‐authors on papers). A Cultural Capability Officer advised on culturally safe practices for Aboriginal and Torres Strait Islander participants. Aboriginal and Torres Strait Islander Peoples, are the First Nations people of Australia. Cultural Capability Officer support refers to the support provided to ensure behaviours, systems and processes are conducted in a way that is culturally respectful. Research is reported in line with the GRIPP‐2 guidelines for reporting patient and public involvement.